TRAINING NEED ANALYSIS (TNA) PETUGAS LAPANGAN KELUARGA BERENCANA (PLKB) PADA BADAN KEPENDUDUKAN KELUARGA BERENCANA NASIONAL PROVINSI BENGKULU - Febriani, Febriani; Yusuarsono, Yusuarsono (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2018)
Training need analysis is a series of activities undertaken to identify problems that arise in the workplace. Training needs analysis is a process of collecting and analyzing data to identify factors that need to be improved through training. The family planning field officer (PLKB) is the spearhead of the existing program implementation in BKKBN. There are several problems PLKB in providing services to the community that is 1. The ability of PLKB in planning, analyzing and evaluating the implementation of the development of prosperous families in the area of work is still not running maximally, 2. Skills to conduct cooperative relationships with all parties terkai less running because there are still many people who do not care about the existing programs in BKKBN, 3. still very weak ability in solving problems encountered in the implementation of its duties. From the problems contained above the importance of training provided by the BKKBN Bengkulu Province to the existing PLKB in various districts in order to have good competence not only hard skills but Soft Skill. The purpose of this research is to describe Traning Need field officer analysis (PLKB) run by BKKBN Bengkulu Province To improve the Competence (Hard Skill & Soft Skill) The PLKB. The method used is descriptive qualitative with technique of selecting informant using Purposive Sampling to determine key informant, technique to collect data that is through observation, interview and documentation, to analyze data obtained in this research using 2 type of encoding that is Open Coding is a section of analysis that specifically explains the relationship between naming and phenomenon categorization through careful examination of data. The coding of terporos (Axial Coding) is a set of data retrieval procedures by creating linkages between categories.